Suitability Analysis of Stone Column Materials with PLAXIS - Saxena, S.; Roy, L. B. (Engineering, Technology & Applied Science Research, 2022)
Stone columns are usually provided in groups to support various geotechnical structures, such as embankments, storage tanks, etc. Several experimental and numerical studies have been performed to study the response of stone columns as soil reinforcement. For relatively moderate loading of a structure, application of stone columns either singly or in groups is widely used. The enhancement of strength of the soil is governed by the type of original subsoil and the properties of the coarse aggregate materials used for the stone columns. Several researchers have analyzed different coarse-grained materials using various plane strain approaches to model the stone columns. This article deals with the non-linear analysis of an isolated stone column embedded in a semi-infinite medium of sandy soil. The parameters which crucially affect the settlement characteristics and the bulging failure of stone columns have been determined. The suitabilities of two different natural aggregates, pebble gravels, and crushed pebble gravels as materials for the stone column have been compared on the basis of their settlement behavior using 2D numerical modeling with the PLAXIS software.